Comparison of Complications in Percutaneous Dilatational Tracheostomy versus Surgical Tracheostomy - Yaghoobi, Siamak (Glob J Health Sci, 2014)
BACKGROUND: Tracheostomy facilitates respiratory care and the process of weaning from mechanical ventilatory support. AIMS: To compare the complications found in percutaneous dilatational tracheostomy (PDT) and surgical tracheostomy (ST) techniques. METHODS: This was a prospective randomized study to evaluate the complications of PDT and ST procedures in patients admitted to ICU unit of a teaching hospital during 2008 to 2011. We studied 40 patients in each group. PDTs were performed with blue rhino technique at the bedside by a skilled clinician and all cases of STs performed by Charles G Durbin technique in operating room under general anesthesia. Bronchoscopic examination through tracheostomy tube was performed to ensure the correct position of tracheostomy tube in the trachea lumen. The duration of procedures and pre- and post-interventional complications were recorded. RESULTS: The most common complications observed in the PDT group were minor bleeding (n=4), hypoxemia, and cardiac dysrhythmias (n=3) whereas in the ST group, the most frequent complications were minor bleeding (n=5) and endotracheal tube puncture (n=3). The difference in overall complications between the two groups was insignificant (P=0.12). CONCLUSION: PDT with blue rhino technique is a safe, quick, and effective method while the overall complications in both groups were comparable.